A Comparative Study on Dyeing Properties of Hemp and Cotton Fiber - Kabir, Shekh Md. Mamun; Karim, Rezaul; Islam, Khayrul (European Scientific Journal, ESJ, 2017)
In this study, a mixed bi-functional reactive dye was applied to the cotton and hemp woven fabrics. Their dyeing and fastness properties were compared. From the results, it was observed that the cotton fabric exhibits better exhaustion and levelness than hemp woven fabrics. The build-up and fastness properties of the two woven fabrics appeared to be almost similar.